2012
DOI: 10.7150/ijbs.4454
|View full text |Cite
|
Sign up to set email alerts
|

CD133+EpCAM+ Phenotype Possesses More Characteristics of Tumor Initiating Cells in Hepatocellular Carcinoma Huh7 Cells

Abstract: Background: EpCAM or CD133 has been used as the tumor initiating cells (TICs) marker in hepatocellular carcinoma (HCC). We investigated whether cells expressing with both EpCAM and CD133 surface marker were more representative for TICs in hepatocellular carcinoma Huh7 cells.Methods: Four different phenotypes of CD133+EpCAM+, CD133+EpCAM-, CD133-EpCAM+ and CD133-EpCAM- in Huh7 cells were sorted by flow cytometry. Then cell differentiation, self-renewal, drug-resistance, spheroid formation and the levels of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 45 publications
(60 reference statements)
8
69
1
Order By: Relevance
“…Prolonged 5-FU treatment has been shown to increase in EpCAM high and CD133 high 5-FU-resistant hepatocellular carcinoma cells (HuH-7; ref17). Hepatocellular carcinoma cells expressing EpCAM and CD133 proteins have been implicated to possess features characteristics of tumor-initiating cells (50). Interestingly, EpCAM high and CD133 high 5-FU-resistant hepatocellular carcinoma cells could be selectively killed by DZNep (17).…”
Section: Discussionmentioning
confidence: 88%
“…Prolonged 5-FU treatment has been shown to increase in EpCAM high and CD133 high 5-FU-resistant hepatocellular carcinoma cells (HuH-7; ref17). Hepatocellular carcinoma cells expressing EpCAM and CD133 proteins have been implicated to possess features characteristics of tumor-initiating cells (50). Interestingly, EpCAM high and CD133 high 5-FU-resistant hepatocellular carcinoma cells could be selectively killed by DZNep (17).…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, these cells were capable of initiating highly invasive HCC in nonobese diabetic, severe combined immunodeficient mice. Chen et al [77] found that CD133(+) EpCAM (+) cells possessed many characteristics of TICs in Huh-7 cells, including higher differentiation capacity, increased colony-formation ability, preferential expression of stem cell-related genes, drug-resistant to some chemothera-peutics, more spheroid formation of culture cells and stronger tumorigenicity in NOD/SCID mice. In 2013, Yamashita et al [78] showed that CSC markers EpCAM and CD90 was independently expressed in liver cancer.…”
Section: Epcammentioning
confidence: 99%
“…Cancer stem cells (CSCs) have been identified in a number of solid tumors, including HCC (2)(3)(4). CSCs may lead to recurrence, drug-resistance and tumor formation in HCC (5).…”
Section: Introductionmentioning
confidence: 99%
“…CSCs may lead to recurrence, drug-resistance and tumor formation in HCC (5). Cluster of differentiation (CD)133 is a membrane-bound pentaspan glycoprotein that has been identified as a surface biomarker in a variety of cancer types, including breast, colon, prostate, pancreatic, lung and liver carcinoma (2,3,(6)(7)(8)(9)(10)(11). Although its function remains unclear, directly targeting CD133 has been demonstrated to be a potentially effective strategy for eliminating CSCs (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation